Pengaruh Bahasa Daerah Terhadap Aktivitas Pembelajaran Geografi di Kelas XII IPS di MA Birrul Walidain NWDI Rensing - Rahmat, Muhammad Fajrur; Ali, Ibrahim; Mas'ad, Mas'ad (Universitas Hamzanwadi, 2025)
Language is an essential tool for communication used by humans as social being to interact with one another. It plays a crucial role in education, from elementary to high school, where language is integral to the learning process. In Indonesia, the presence of numerous regional languages across different regions has led to the coexistence of Bahasa Indonesia as the national language and as the medium of instruction in education. This coexistence creates a unique dynamic in both social interactions and learning processes. This study focuses on the impact of regional language use, particularly Sasak, on geography learning activities at MA Birrul Walidain NWDI Rensing, East Lombok, West Nusa Tenggara. Based on initial observations, it was found that most students are more proficient in using their regional language than Bahasa Indonesia, which results in a lack of student engagement during lessons, particularly in geography